PERLINDUNGAN HUKUM BAGI DEBITUR TERHADAP TARIF SEWA MODAL (BUNGA) PADA USAHA PERGADAIAN DI KOTA PEKANBARU - Nana Satun Nazirah; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Legal protection for borrowers against rental rates of capital (interest on payable busines,to high interest that there are restrictions on determining interest based on jurisprudene No. 12 / Pdt-G / 2016 / PN Blk in the jurisprudence provides restrictions on achieving asense of security and Justice so as to avoid the practice of usury, and not to abuse the tate of the debtor when borrowing money. What is meant by the protection of the law is a provision of assurance or certainty that a person will get what has become the rights and obligations, so that the person feels safe Based on the above The objectives of thesis writing are: firstly, to know how the legal protection is like the debtor to the rental rate of capital (interest) on the pawnshop business Secondly, to know the factors that make difficulty of setting the rental rate of capital (interest) on the business of pawn in the city of Pekanbaru.This type of research can be classified as a type of sociological law research. This research is descriptive, a research that describes clearly and detailed about legal protection for debtors to the rental rate of capital (interest) on the business of pawnshop in the city of Pekanbaru. Sources of data used are primary data and secondary data consisting of primary legal materials, secondary law materials and tertiary legal materials, data collection techniques in this study with interviews, questionnaires, observation and literature review, after the data collected and then analyzed to be drawn conclusions .From the results of research and discussion it can be concluded first that, Based on jurisprudence No. 12 / Pdt.G / 2016 / PN Blk states that in Article 1767 The Second Criminal Code allows an agreement to determine interest in excess of the law At that time determined at 6% per year according to the Panel of Judges for the principle of justice, the principle of propriety and public order then the determination of the amount of interest should be a guide even for individuals who run the practice of borrowing money with interest in order not to support the practice of usury in society that can abuse the state of society Which is squeezed in need of money.Keywords: Legal Protection - Debtor - Interest - Pawn